2015
DOI: 10.1096/fj.15-280313
|View full text |Cite
|
Sign up to set email alerts
|

WNT5a is required for normal ovarian follicle development and antagonizes gonadotropin responsiveness in granulosa cells by suppressing canonical WNT signaling

Abstract: Whereas the roles of the canonical winglesstype MMTV (mouse mammary tumor virus) integration site family (WNT) signaling pathway in the regulation of ovarian follicle growth and steroidogenesis are now established, noncanonical WNT signaling in the ovary has been largely overlooked. Noncanonical WNTs, including WNT5a and WNT11, are expressed in granulosa cells (GCs) and are differentially regulated throughout follicle development, but their physiologic roles remain unknown. Using conditional gene targeting, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 61 publications
6
39
0
Order By: Relevance
“…We have shown that reduced ovulation observed in APC2-deficient mice is not caused by defects in ovulation and terminal differentiation of granulosa cells (which happen when WNT signalling is activated in antral follicles), but rather caused by restricted follicular growth and failure to reach the preovulatory stage. This phenotype is similar to previous phenotypes published when WNT Mohamed et al APC2 in ovarian homeostasis and tumourigenesis 13 signalling was activated in pre-antral follicles (16,17), implying that APC2 activity is required in growing follicles as early as the pre-antral stage.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We have shown that reduced ovulation observed in APC2-deficient mice is not caused by defects in ovulation and terminal differentiation of granulosa cells (which happen when WNT signalling is activated in antral follicles), but rather caused by restricted follicular growth and failure to reach the preovulatory stage. This phenotype is similar to previous phenotypes published when WNT Mohamed et al APC2 in ovarian homeostasis and tumourigenesis 13 signalling was activated in pre-antral follicles (16,17), implying that APC2 activity is required in growing follicles as early as the pre-antral stage.…”
Section: Discussionsupporting
confidence: 90%
“…The current findings also extend our knowledge of deleterious effects of WNT signalling activation on ovarian homeostasis and fertility (10,(15)(16)(17). We have shown that reduced ovulation observed in APC2-deficient mice is not caused by defects in ovulation and terminal differentiation of granulosa cells (which happen when WNT signalling is activated in antral follicles), but rather caused by restricted follicular growth and failure to reach the preovulatory stage.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The PI3K/AKT signaling pathway can also activate the WNT/CTNNB1 pathway through inactivation of GSK3β [ 50 ]. Both Wnt4 flox/- ;Amhr2 tm3(cre)Bhr/+ and Wnt5a flox/- ;Amh2 cre/+ mice are subfertile and have small ovaries, follicle atresia, and a decreased ovulation rate, indicating that the WNT signaling pathway is important in ovarian follicle growth/survival and steroidogenesis [ 51 52 53 54 55 ]. Catnb flox(ex3)/+ ;Amhr2 Cre/+ mice, which express stable nuclear β-catenin driven by the Amhr2 promoter, develop GCTs, suggesting the importance of the misregulated Wnt/β-catenin pathway in GCT development [ 56 ].…”
Section: Introductionmentioning
confidence: 99%